Sound and Vibration Behavior Assessment of Different Sizes of Waste Tyre Rubber in Natural Rubber Composites for Damping Applications - Velu Chandran (Science Faculty of Chiang Mai University, 2019)
The different micro sizes of waste tyre rubber (WTR) and nano precipitated silica filled natural rubber composites were investigated to evaluate the sound and vibration damping behavior. In this, WTR particles were prepared in three different sizes (100-250 mm, 550-700 mm and 1000-1150 mm) using ambient grinding process. Then the particles blended with natural rubber and silica compounds, and the blend was synthesized by two roll mill and hydraulic press open vulcanization. The composite material samples were ranged from 0 to 40phr of WTR loading in each size and silica loading fixed at 20phr. The various proportions of samples in all sizes were characterized in respect of their sound and vibration damping behavior and these were evaluated by plane wave impedance tube and cantilever beam free vibration method respectively. Results indicated that sound absorption of small sizes of WTR showed comparatively higher with other sizes used. The morphological study revealed that small particles resulted better cross link chains and less weaker bonds which leads to higher sound absorption coefficient. The results of large sizes of WTR filled natural rubber composites showed excellent vibration damping performance compared with other sizes used. Thermal behavior showed that the energy absorption was more with the use of large WTR than other sizes used which led to increase the damping characterization. Owing to better damping, WTR filled natural rubber composites accurately used in the applications where damping is considered as important design criterion.